2020
DOI: 10.1101/gr.261941.120
|View full text |Cite
|
Sign up to set email alerts
|

Long-read sequencing for non-small-cell lung cancer genomes

Abstract: Here, we report the application of a long-read sequencer, PromethION, for analyzing human cancer genomes. We first conducted whole-genome sequencing on lung cancer cell lines. We found that it is possible to genotype known cancerous mutations, such as point mutations. We also found that long-read sequencing is particularly useful for precisely identifying and characterizing structural aberrations, such as large deletions, gene fusions, and other chromosomal rearrangements. In addition, we identified several me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…For the purpose of long-read sequencing, we employed a nanopore sequencer. A nanopore sequencer can potentially read DNA molecules that are longer than 100 kb ( 10 ). It has also been reported that modifications in DNA and RNA can be detected from the electric signal patterns observed for mC of DNA and RNA, hmC of DNA, and unmethylated C ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of long-read sequencing, we employed a nanopore sequencer. A nanopore sequencer can potentially read DNA molecules that are longer than 100 kb ( 10 ). It has also been reported that modifications in DNA and RNA can be detected from the electric signal patterns observed for mC of DNA and RNA, hmC of DNA, and unmethylated C ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the advantages of long-reads and real-time sequencing have made Nanopore sequencing an effective tool to detect genomic and genetics aberrations such as DNA structural variants and RNA alternative splicing events [53]. Nanopore sequencing have demonstrated its powerful capability of detecting structural variation in lung cancer [54, 55], leukemia [56], and neuron disorder [5759], and it has been applied to clinical samples for molecular etiology or diagnosis of genomic variants relevant disease [57–62]. Meanwhile, Nanopore sequencing of splicing changes has been utilized in cancer research such as breast cancer [63], leukemia [64, 65], and brain tumor [66].…”
Section: Discussionmentioning
confidence: 99%
“…Base calling of the FAST5 data from MinION was performed using Albacore 2.2.7 and Guppy v3.3.0, then was converted into FASTQ files. Only 1D reads for the following analyses [ 62 ]. Reads were aligned to the reference human genome, GRCh38, using Minimap2 (v2.2.14) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%